2019
DOI: 10.1029/2019wr025726
|View full text |Cite
|
Sign up to set email alerts
|

Fill and Spill Hillslope Runoff Representation With a Richards Equation‐Based Model

Abstract: Integrated surface‐subsurface hydrological models (ISSHMs) are well established numerical tools to investigate water flow and contaminant transport processes over a wide range of spatial and temporal scales. However, their ability to correctly reproduce the response of hydrological systems to natural and anthropogenic forcing depends largely on the accuracy of model parameterization, including the level of detail in the representation of the bedrock. This latter is typically incorporated in some way via the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…From a mechanistic viewpoint, the trench data have been applied in a series of modelling studies. Some of these examined whether a Richards equation‐based model, such as Hydrus 3D (Hopp & McDonnell, 2009), Hydrogeosphere (Ameli et al, 2015), or CATHY (Camporese et al, 2020) could reproduce the threshold response. The observation of a threshold provided a strong test of finite element models—can the physics specified at the small scale (i.e., at the finite element scale) capture the emergent behaviour of a threshold response at the hillslope scale?…”
Section: Unsolved Scientific Problems In Hydrology and Insights Beyond The Idiosyncrasies Of Pmrwmentioning
confidence: 99%
“…From a mechanistic viewpoint, the trench data have been applied in a series of modelling studies. Some of these examined whether a Richards equation‐based model, such as Hydrus 3D (Hopp & McDonnell, 2009), Hydrogeosphere (Ameli et al, 2015), or CATHY (Camporese et al, 2020) could reproduce the threshold response. The observation of a threshold provided a strong test of finite element models—can the physics specified at the small scale (i.e., at the finite element scale) capture the emergent behaviour of a threshold response at the hillslope scale?…”
Section: Unsolved Scientific Problems In Hydrology and Insights Beyond The Idiosyncrasies Of Pmrwmentioning
confidence: 99%
“…Fenicia et al (2016), however, found that functioning units discretized using geology better reproduce flow dynamics than topography-based discretization. Camporese et al (2019) showed that soil-bedrock interfaces need to be accurately represented to predict subsurface interflow. Similarly, Ajami and Sharma (2018) and Xiao et al (2019) emphasized the predominant control of soil properties in streamflow generation compared to topography and catchment size.…”
Section: Upscaling With Representation Of Multiple Landscape Functioning Unitsmentioning
confidence: 99%
“…For instance, certain studies simply assumed bedrock to be impermeable (i.e. a no-flow boundary was imposed at its upper surface; Ala-aho et al, 2017;Camporese et al, 2019). Alternatively, single bedrock zones with homogeneous hydraulic conductivity (Markovich et al, 2016;Voeckler et al, 2014) or a few sub-parallel geological layers (Huntington & Niswonger, 2012) have been considered sufficient, although Engdahl and Maxwell (2015) did employ a fuller representation.…”
Section: Introductionmentioning
confidence: 99%